“The Companion of War”: Dysentery in Bonaparte’s Army of the Orient (1798–1801) - Tchoudinov, Alexander V. (Izvestiâ Uralʹskogo federalʹnogo universiteta. Seriâ 2, Gumanitarnye nauki, 2023)
The history of wars provides abundant material for the study of epidemics since they have often accompanied military conflicts. The Revolutionary and Napoleonic Wars of France are especially interesting for researchers due to their duration, the geographical diversity of theaters of military operations, and the large number of participants. The first Russian studies on “Napoleonic epidemiology” published recently show that this era opens wide opportunities to historians in this regard. The author of this article follows in line with such studies, trying to identify the causes and features of the epidemic of dysentery in Bonaparte’s troops which occupied Egypt in 1798–1801, and to establish what impact the epidemic had on the course of the expedition. The doctors of the Army of the Orient were initially very afraid of plague, which they had not dealt with before their arrival in Egypt. Dysentery was well known to them, as people often contracted it in France. To combat the disease, they had a set of tools that had been used more or less successfully for decades in Europe. However, in practice, the epidemic of dysentery turned out to be so deadly in the Army of the Orient that in terms of the death toll, it could be compared with plague, if not even surpassed it. According to the author, the reason for such a high lethality of this disease was the fact that in Egypt, it was caused by another, more pathogenic carrier than in France, and the fact that French doctors could designate several intestinal diseases endemic to Egypt and similar to dysentery with a single concept of “dysentery”, which they had no experience in combating with. French doctors did not use hygiene measures that could prevent the spread of this disease, because they were guided by erroneous ideas about the etiology of dysentery, considering it a consequence of hypothermia of the body.